A Conceptual Review of Timira with special reference to Presbyopia - Vardhan, Prabhakar; Sharma, Sanjeev; Fiaz, Shamsa (International Research Journal of Ayurveda & Yoga, 2022)
Shalakya Tantra is an Ayurvedic branch also known as ’Urdhvanga Chikitsa’ since it focuses on the upper body. The eye is a highly specialised sense organ that primarily serves the function of vision. The most important of all the senses is vision. Almost 90% of knowledge is only perceived via the eyes. Humans rely on eyesight for the majority of their daily tasks. As a result, any impediment to this is a significant disadvantage. As long as one is living, Ayurveda recommends making every effort to protect one’s eyes. Clinical symptoms associated to visual disturbances are commonly encountered in Drishtigata Rogas in Ayurveda. As a result, all cases of visual disturbance can be grouped together under the Timira Kacha-Linganasha complex. Doshas lodged in the first and second patala produce symptoms such as avyaktadarshan and difficulties seeing up close. These symptoms are quite similar to the cardinal signs of presbyopia, which is characterised by a physiological insufficiency of accommodation that leads to a progressive loss of near vision. It was noted by ancient acharyas as a result of growing age. Today’s erroneous lifestyle is causing premature ageing consequences such as presbyopia, where Ayurveda science’s wholesome and rejuvenate approach might help humanity. Hence, Ayurvedic science can be explored to find a better way to manage this ailment. Pathykaraaharvihar, various Rasayana Yoga, Chakshusya medicines, Netrakarma, Kriyakalpa, Panchkarma, and other preventive and therapeutic treatments are described in Ayurveda to treat Timir.